Multiple-victim body contact water rescues - Miller, D. I.; Dahl, A. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Water accidents remain one of the leading causes of accidental death in Canada and the United States. Although reasonable volumes of literature have been accumulated on drowning statistics, physiological effects of drowning, and treatment of near-drowning (Modell, 1978), little is known of the details of successful water rescues (Miller and McQueen, 1978). Although lifesaving organizations, such as the American Red Cross, the Royal Life Saving Society, and the YMCA, teach methods of rescue, there is a lack of data to indicate whether or not the techniques taught are being used in actual emergency situations and whether or not they are effective.